2021
DOI: 10.1080/0305764x.2021.1876840
|View full text |Cite
|
Sign up to set email alerts
|

Initial English language teacher education: the effects of a module on teacher research

Abstract: Framed in action research, the authors investigated the perceptions and experiences of a cohort of student-teachers as they learned about and explored for the first time teacher research in a selfcontained module as part of a four-year pre-service or initial English language teacher education (IELTE) programme in southern Argentina. The module, 'Research in English Language Teaching', ran from March-November 2018. It was led by a teacher educator based in Argentina and a UK-based colleague who acted as an exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
(46 reference statements)
1
13
0
Order By: Relevance
“…Another theme emerged from the literature review is related to the reconstruction of teacher identity (e.g., Banegas & Consoli, 2021;Capobianco & Ríordáin, 2015;Dikilitaş & Çomoglu, 2022;Levin & Rock, 2003;Price, 2001;Smith & Sela, 2005;Trent, 2010). The research suggests that AR creates a space for reflection and questioning that allows PSTs to work on the discrepancy between vision and reality, which could engage them in a process of identity formation.…”
Section: (Re)construction Of Teacher Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…Another theme emerged from the literature review is related to the reconstruction of teacher identity (e.g., Banegas & Consoli, 2021;Capobianco & Ríordáin, 2015;Dikilitaş & Çomoglu, 2022;Levin & Rock, 2003;Price, 2001;Smith & Sela, 2005;Trent, 2010). The research suggests that AR creates a space for reflection and questioning that allows PSTs to work on the discrepancy between vision and reality, which could engage them in a process of identity formation.…”
Section: (Re)construction Of Teacher Identitymentioning
confidence: 99%
“…The studies reviewed have revealed that participation in AR projects (re)constructs PSTs' understanding of research and improves their research skills (e.g., Aras, 2021;Banegas & Consoli, 2021;Faikhamta & Clarke, 2015;Trent, 2010;Ulvik et al 2018;Yan, 2016). For example, in the context of a four-year pre-service ELT program in southern Argentina, Banegas and Consoli (2021) explored the impact of a mandatory research module which aimed to help PSTs gain a research mindset by giving them the opportunity to conduct individual AR projects. The results indicated that the PSTs' traditional views of research were challenged and reconstructed as they saw how AR bridged the gap between theory and practice.…”
Section: (Re)conceptualization Of Researchmentioning
confidence: 99%
“…Acknowledging, respecting, and valuing these professional identities does not constitute the end of good, meaningful research for the language education community. After all, despite some concerns about the validity of language education research for 'real world' issues and practices (e.g., Ushioda, 2020), there is evidence which fuels the hope that strong collaborative endeavours between traditional academic researchers, teachers and practitioner researchers are possible (e.g., Banegas and Consoli 2021;Dikilitaş and Wyatt 2018). After all, the rich tradition of Action Research in language education shows that teachers are capable agents of change who can generate powerful transformations and insights through research engagement.…”
Section: Who Are Language Education Researchers and What Do They Actually Do?mentioning
confidence: 99%
“…Dörnyei (2007), for instance, lamented that most Action Research projects were conducted by teachers engaged in a postgraduate programme that involves a research component. This is echoed by Banegas and Consoli (2021) who also noted a dearth of pre-service or junior teachers who explore the value of research because research engagement tends to happen at postgraduate level, and even then, issues of privilege (e.g.,financial status and social class) may compromise some teachers' access to postgraduate programmes and research training.…”
mentioning
confidence: 99%
“…Language teacher education (LTE), which spans a wide variety of topics and perspectives, has been extensively researched since the 1990s [1][2][3][4][5][6][7]. As an important agenda, language teacher professional quality has gained in popularity in LTE research [8][9][10], particularly along with some updated teaching methods including communicative language teaching (CLT), and more recently task-based language teaching (TBLT) and content and language integrated learning (CLIL).…”
Section: Introductionmentioning
confidence: 99%